2008
DOI: 10.1007/s00198-008-0748-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of falls among postmenopausal women: results from the National Osteoporosis Risk Assessment (NORA)

Abstract: This large cohort had sufficient power to identify 18 risk factors that independently predicted a significantly increased risk of falling with a graded increase in risk with increasing number of risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
3
16

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 47 publications
4
57
3
16
Order By: Relevance
“…If TSH !0.20 mU/l, free thyroxine (FT 4 ) and total triiodothyronine (T 3 ) were measured, and if TSH O4.0 mU/l, FT 4 and thyroid peroxidase antibodies (TPOAb) were measured. FT 4 was measured by DELFIA FT 4 (total analytical variation !7%, reference range 8-20 pmol/l), T 3 by AutoDELFIA T 3 (total analytical variation !7%, reference range 1.2-2.7 nmol/l) and TPOAb by luminoimmunoassay from B.R.A.H.M.S.…”
Section: Thyroid Function Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…If TSH !0.20 mU/l, free thyroxine (FT 4 ) and total triiodothyronine (T 3 ) were measured, and if TSH O4.0 mU/l, FT 4 and thyroid peroxidase antibodies (TPOAb) were measured. FT 4 was measured by DELFIA FT 4 (total analytical variation !7%, reference range 8-20 pmol/l), T 3 by AutoDELFIA T 3 (total analytical variation !7%, reference range 1.2-2.7 nmol/l) and TPOAb by luminoimmunoassay from B.R.A.H.M.S.…”
Section: Thyroid Function Testsmentioning
confidence: 99%
“…Hypothyroidism is a risk factor for falls in elderly individuals (4), and hyperthyroidism has for more than a century been known as a risk factor for osteoporosis (5). Both overt hypothyroidism and hyperthyroidism have been associated with increased risk of fractures in previous studies (6,7,8,9,10,11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…While it is an established risk factor for osteoporosis and would generally trigger screening, 9 this study showed advancing age to be associated with a decreased likelihood of completing the screening test; women aged 80 years or older are less likely to be screened. Indeed, increasing age by itself has been identified as a barrier to effective osteoporosis care, along with the presence of dementia, lack of treatment adherence, and inadequate social support among vulnerable elderly patients.…”
Section: Discussionmentioning
confidence: 96%
“…As mentioned above, ZOL increases BMD, and thus it could reduce the risk of falls to a certain extent. On the other hand, it is known that osteoporosis can lead to spinal deformities such as thoracic kyphosis due to vertebral compression that alters the structure of the spine, causing weakness of the extensor muscles of the trunk and leading to reduced physical mobility and flexibility [33]. When ZOL increases BMD and improves the bone status, the extensor muscles of the trunk are also improved.…”
Section: Rycina 2 śRednie Liczby Punktów W Poszczególnych Domenach Kmentioning
confidence: 95%